On the genus Ammonius Thorell, 1899 (Mygalomorphae, Barychelidae): description of the female of A. pupulus, a new species and new distribution records - Gonzalez-Filho, Hector M.O. [UNESP]; Guadanucci, José Paulo L. [UNESP]; Brescovit, Antonio D. (Museum National D'Histoire Naturelle, 2023)
Among the 40 genera of Barychelidae, only nine genera are described from the African continent. Thorell (1899) described Ammonius Thorell, 1899 based on a male from Cameroon. In 1965 Benoit added more information from the holotype, with detailed illustrations of the male palp bulb and the eye group. Since then, few taxonomic revisions or new species of Barychelidae have been proposed from the African continent. Ammonius can be distinguished by the strongly pronounced retrolateral lobe of the male cymbium and the aspect of the bilobed spermathecae of the female. We redescribe the holotype male of A. pupulus Thorell, 1899 and describe the female for the first time. Additionally, a new species is described: Ammonius benoiti sp. nov., from Ivory Coast. The morphology of the tarsal setae is presented through SEM photographs. New distribution records of the genus are provided.
Keywords: Arachnid; Cameroon; new records; Western Africa